Validation of the Korean Version of the 24-Item Early-Onset Scoliosis Questionnaire: A Multicenter Study from the Korean Research Society of Spinal Deformity - Hwang, Chang Ju; Chang, Sam Yeol; Park, Kun-Bo; Lee, Dong-Ho; Cho, Jae Hwan; Matsumoto, Hiroko; Park, Sehan (Clinics in orthopedic surgery, 2025)
A 24-item early-onset scoliosis questionnaire (EOSQ-24) has been developed as a valid tool for assessing the physical and emotional function of patients with early-onset scoliosis (EOS). Previous studies that conducted transcultural adaptation of the original EOSQ-24 into other languages have demonstrated the high reliability of the questionnaire. However, a Korean version of the EOSQ-24 is not available, limiting optimal patient assessment in this nation. Therefore, this study was conducted to develop and validate a Korean version of EOSQ-24. The original English version of the EOSQ-24 was cross-culturally adapted following standard guidelines. The final version of the Korean EOSQ-24 was prospectively applied to a group of patients who were native Korean speakers. Internal consistency was evaluated using the Cronbach α coefficient and item-total correlations. The mean, standard deviation, floor effect, and ceiling effect of each item were also assessed. A total of 102 caregivers of patients with EOS (45 males and 57 females) completed the Korean EOSQ-24. The patients' average age was 6.39 ± 2.16 years. The Cronbach α coefficient for the 24-item scale was 0.942, indicating excellent reliability. The corrected item-total correlation coefficients ranged between 0.449 and 0.788. The mean value of the EOSQ-24 questionnaire was 3.19. Floor and ceiling effects for all questionnaires were below 30%, which could be considered acceptable. Our study successfully developed and validated the Korean version of the EOSQ-24, providing a reliable instrument for assessing the physical and emotional well-being of patients with EOS and their caregivers in the Korean context. The widespread adoption of the Korean EOSQ-24 in clinical practice and research settings can enhance the quality of care and improve outcomes for individuals affected by EOS in Korea.